1991
DOI: 10.1128/jb.173.18.5763-5770.1991
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Escherichia coli sohB gene, a multicopy suppressor of the HtrA (DegP) null phenotype

Abstract: We cloned and sequenced the sohB gene of Escherichia coli. The temperature-sensitive phenotype of bacteria that carry a Tn10 insertion in the htrA (degP) gene is relieved when the sohB gene is present in the cell on a multicopy plasmid (30 to 50 copies per cell). The htrA gene encodes a periplasmic protease required for bacterial viability only at high temperature, i.e., above 39 degrees C. The sohB gene maps to 28 min on the E. coli chromosome, precisely between the topA and btuR genes. The gene encodes a 39,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 37 publications
2
28
0
1
Order By: Relevance
“…Another approach to characterizing the cellular functions of the wild-type genes which are mutated is to screen for multicopy suppressor genes (1,3,23,29). Very recently, we identified a multicopy suppressor gene of smbA mutation, named mssA, that maps at 21 min, just upstream of the rpsA gene on the E. coli chromosome (48).…”
Section: Suppressor Mutation Of the Mukb Null Mutantmentioning
confidence: 99%
“…Another approach to characterizing the cellular functions of the wild-type genes which are mutated is to screen for multicopy suppressor genes (1,3,23,29). Very recently, we identified a multicopy suppressor gene of smbA mutation, named mssA, that maps at 21 min, just upstream of the rpsA gene on the E. coli chromosome (48).…”
Section: Suppressor Mutation Of the Mukb Null Mutantmentioning
confidence: 99%
“…at 37 uC or in the presence of puromycin), we observed that our double mutant has a lower growth rate than the trmA-clpP mutant (data not shown). Alternatively, htrA suppressors might have arisen, as previously shown in Escherichia coli, where sohA and sohB are multi-copy suppressors of htrA (Baird & Georgopoulos, 1990;Baird et al, 1991).…”
mentioning
confidence: 99%
“…Prc is a protease that processes the C terminus of FtsI (penicillinbinding protein 3) and is required for protection from combined thermal and osmotic stress (20). The sppA gene and probably the sohB gene encode homologous proteases that degrade signal peptides after their processing (4,22). Additionally, the outer membrane-bound protease OmpT (protease VII) is specific for substrates with paired basic residues (55).…”
mentioning
confidence: 99%